(untitled) (Kinesiology, 2023)
Ankle weight loading is a straightforward and easily applicable method to increase the physiological burden during walking in older adults. The current study investigated the acute effects of ankle weight loading on the regional activity of rectus femoris (RF) muscle and lower-extremity joint angles during walking in twenty-nine healthy older adults. Neuromuscular activities of proximal (RFP) and distal (RFD) regions of the RF into averaged rectified values (ARV) and kinematics of left lower extremities were measured during walking with and without ankle weight on a treadmill using surface electromyography (EMG) and motion capture, respectively. Significant differences in normalized ARV between RFP and RFD with ankle weight loading were found in longer periods of the stance phase (30-55 and 5-15%) and swing (70-90 and 95-100%) phases compared to without weight condition (30-40, 50, and 75-85%) (p<.05). The hip flexion angle at (10-25 and 60-90%), knee extension at (5%, 15%, 25-35%, and 100%), and ankle dorsiflexion at (30-55% and 75%) of the gait cycle were increased with ankle weight loading more than without it (p<.05). Ankle weight loading could change the neuromuscular activity pattern of RFP and improve lower-extremity kinematics during walking in older adults. Key words: the elderly, ankle weight, rectus femoris, surface electromyography, joint angle